Heterogeneity in firm performance during economic crisis - Pittiglio, Rosanna; Bruni, Sergio; Reganati, Filippo (Business, Management and Economics Engineering, 2014)
What happens to firms during periods of deep economic crisis? Did different types of firms perform differently under the economic crisis? With the aid of a rich database and focusing on the literature regarding the growth of firms, this paper investigates the relative profitability performance of Italian firms during the current economic crisis, exploring those factors, which help certain firms to do relatively better even in the slowdown period. Some preliminary results show that the Italian firms that are relatively young in age, with relatively better current liquidity and more focused on domestic market have performed better than other firms. Furthermore, firms operating in high-tech and in highly concentrated sectors have enjoyed a better performance in this period.